Influence of financial performance, company characteristics and good corporate governance on sustainability reporting disclosure - Wiharno, Herma; Syarifudin, Syahrul; Fitriani, Chintia; Dina, Hestika Puspa (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to determine the Effect of Financial Performance, Company Characteristics and Good Corporate Governance on Sustainability Reporting Disclosure in Banking Sector Companies. The method used in this research is descriptive method and verification method. The sample obtained is 102 data. The data analysis technique used is panel data regression analysis. Based on the results of data analysis obtained, Profitability, Liquidity, Solvency, Activity, Company Age, Audit Committee and Independent Board of Commissioners simultaneously have a significant effect on Sustainability Reporting Disclosures. Partially, profitability has a significant positive effect on Sustainability Reporting Disclosures. Liquidity has a significant positive effect on Sustainability Reporting Disclosures. Solvency has a significant positive effect on Sustainability Reporting Disclosure. Activities have a significant positive effect on Sustainability Reporting Disclosure. Company age has a significant positive effect on Sustainability Reporting Disclosure. The Audit Committee has a significant positive effect on the Disclosure of Sustainability Reporting. The Independent Board of Commissioners has a significant positive effect on Sustainability Reporting Disclosure.